2007
DOI: 10.1021/la701145q
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bromide Ions in Charge-Stacked Zwitterionic Micellar Systems

Abstract: A novel zwitterionic surfactant, N-dodecyl-N,N,N',N'-tetra-methyl-ethylene-di-ammonio-propane-sulfonate bromide (DEPB), has been synthesized, and Br(-) involved in the micellar system has been characterized by potentiometry, NMR, and X-ray absorption fine structure (XAFS). Although the dissociation degree of Br(-) from the micelle evaluated by potentiometry almost agrees with that determined by NMR, the former is significantly smaller than the latter over the entire range of concentrations of DEPB. This is exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Also, effects of the structures of anion-exchange groups can be seen; zwitterionic surfactant molecules appear to facilitate the dehydration of Br -in comparison with the trimethylammonium group. [63][64][65] This implies that Br -is more effectively shielded from a bulk solution by the propylene sulfonate groups. In particular, an NMR study has elucidated that Br -is delocalized on the inside ammonium group in the N-dodecyl-N,N¢-tetramethylethylendiammonium-N¢-propane sulfonate micelle.…”
Section: Ion Recognition Selectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Also, effects of the structures of anion-exchange groups can be seen; zwitterionic surfactant molecules appear to facilitate the dehydration of Br -in comparison with the trimethylammonium group. [63][64][65] This implies that Br -is more effectively shielded from a bulk solution by the propylene sulfonate groups. In particular, an NMR study has elucidated that Br -is delocalized on the inside ammonium group in the N-dodecyl-N,N¢-tetramethylethylendiammonium-N¢-propane sulfonate micelle.…”
Section: Ion Recognition Selectivitymentioning
confidence: 99%
“…In particular, an NMR study has elucidated that Br -is delocalized on the inside ammonium group in the N-dodecyl-N,N¢-tetramethylethylendiammonium-N¢-propane sulfonate micelle. 64 Thus, Br -is taken up into the interior of the monolayer or aggregates of the zwitterionic surfactants and is dehydrated to a greater extent possibly because of water-shortage circumstances.…”
Section: Ion Recognition Selectivitymentioning
confidence: 99%
“…Also, revealing the local structures of ions below and above t eu should allow the discussion of a phase transition on a molecular basis. We have studied the local structures of Br − by X-ray absorption fine structure (XAFS) in an anion-exchange resin, , on a cationic micellar surface, , on a cationic Langmuir monolayer, , and in concentrated aqueous polyethyleneglycol, , and have revealed that hydrated Br − can release some water molecules from its first hydration shell under some conditions. When the temperature of salt-doped ice is raised above the eutectic temperature ( t eu ) of the system, a liquid phase starts to emerge.…”
Section: Introductionmentioning
confidence: 99%
“…And it is estimated that the influence of the anion site on the retention properties is not strong. Okada and co‐workers reported that the partition of ions to zwitterionic surfaces depends on the nature of analyte anions, and is not strongly affected by analyte cations . Analyte anions having a lower hydration property tend to associate directly with the cation sites of the zwitterionic functional group.…”
Section: Resultsmentioning
confidence: 99%